The Study Of Organizational Factors Affecting The Application Of Information Technology By Middle Managers In TUMS Hospitals - Hossein Barzekar; Reza Safdari; Mohammad Reza Eshraghiyan; Hossein Dargahi (پیاورد سلامت, 2013)
Background and Aim: One of the most important reasons why organizations are distinguished from each other is the extent to which each applies information technology. Among the most important factors playing a role in the application of information technology are organizational factors such as organizational resources, organizational knowledge, processes, management structure, values and goals all these elements affect the level of information technology acceptance and application. Therefore, this study aims to determine the degree to which the above-mentioned elements can affect the application of information technology by middle managers of Tehran University of Medical Sciences (TUMS) teaching hospitals.  Materials and Methods: This is a cross-sectional, descriptive-analytic study conducted in 2010. The subjects comprised 110 middle managers of TUMS teaching hospitals. The data-collection instrument was a questionnaire structured by the researchers, and its validity and reliability were confirmed prior to the study. The response rate was 80%.  Results: The participants consisted of 56 (62.9%) males and 33 (37.1%) females. The findings of the study showed that there was a statistically significant relationship between organizational resources, organizational knowledge, processes, management structure, values and goals on the one hand and the application of information technology in TUMS hospitals on the other (p<0.01).  Conclusion: The results show that organizational factors have a considerable impact on the application of information technology. Besides, managers and experts should consider the important aspects and effects of these organizational factors.